Socio-Economic Aspects of Traditional Agroforestry Practice in Two Vlllages in Vientiane Province, Lao People's Democratic Republic - Phandanouvong, Khamphout (1998)
Agroforestry is a general concept for a land management system combining trees and agriculture crops or livestock and it is being practised in a number of ways or techniques. Each of these techniques is adjusted to a specific set of socio-economic factors. Agroforestry cultivators or managers belonging to varying social strata and institutional grouping may practice different forms of agroforestry, even within the same general region. Agroforestry is a traditional practice in almost all of Asia. It has been practised in Laos for hundreds of years. However, it bas not been organised and managed in a systematic and scientific manner. This study evaluated the agroforestry practices in two villages in Vientiane, Lao PDR. The objectives of the study were: (i) to describe some agroforestry practices being practised in the two villages, in Vientiane Province, Laos and (ii) to examine the bio-physical and socio-economic aspects in relation to agroforestry practices in the two villages.